How Chegg Blew Up Our Exams - Samela, Crystal; Martin, Heather (Canadian Perspectives on Academic Integrity, 2021)
Join the presenter for an experience-based discovery about the file-sharing giant Chegg. Engage in one institutions journey when they learned many of their exams were virtually compromised, how they addressed the issue, and how they moved forward. During this session the Chegg Honor Code investigation will be described, and the results shared.